PERCEPTION OF THE RATE OF CHANGE IN A PATIENT'S CONDITION AS A METHOD OF ESTIMATING PROGNOSIS: A PILOT STUDY. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Grogan, Eleanor; Peel, Tim; Regnard, Claud; Paes, Paul
Abstract : Background: Estimation of prognosis is a common request. Many methods have been considered but are often complex or unreliable. Some palliative medicine physicians feel the best guide may be the recent rate of change in physical condition. For example, if a patient perceives their condition has been changing weekly they may have a prognosis of weeks; if day by day the prognosis is likely to be days. No research has been done to show whether this is an accurate guide, despite it being widely used . Methods: Adults with cancer admitted to an NHS inpatient specialist palliative care unit were recruited (exclusion criteria: 1. lacking capacity; 2. if it was thought the study may cause unnecessary distress). Patients were asked "how has your condition changed recently?" (plus a further probe of "do you think things have been changing daily/weekly/monthly?" if required) but were not asked directly about prognosis. Ethics approval was obtained. Data was collected on patient's perception of rate of change, consultant's estimate of prognosis and actual survival time. Aim: To determine whether the proposed research question was a reliable indicator of survival time. Results: Eight patients were recruited. There was similarity between patient perceived rate of change, doctor prognosis estimate and actual survival time in most cases. Numbers were smaller than anticipated due to concerns about causing distress in patients, although this did not occur in participating patients.